2019
DOI: 10.1007/s11306-019-1576-4
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolomics in real-time monitoring of treatment induced toxicity and cachexia in head and neck cancer: a method for early detection of high risk patients

Abstract: Introduction Nutritional treatment in head and neck squamous cell carcinoma cancer (HNSCC) patients undergoing radio-/chemo-radiotherapy (RT/CHRT) is complex and requires a multidisciplinary approach. In this study the real-time dynamic changes in serum metabolome during RT/CHRT in HNSCC patients were monitored using NMR-based metabolomics. Objectives The main goal was to find the metabolic markers that could help prevent of acute radiation sequelae (ARS) escalation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…As a systematic analyzing tool for profiling metabolites, metabolomics was characterized for high resolution, sensitivity, and throughput in detecting a large population of molecules in various biological samples (8)(9)(10). In the last decade, the advance in metabolomic techniques allowed the identification of numerous individual chemicals in a small volume of biofluid.…”
Section: Introductionmentioning
confidence: 99%
“…As a systematic analyzing tool for profiling metabolites, metabolomics was characterized for high resolution, sensitivity, and throughput in detecting a large population of molecules in various biological samples (8)(9)(10). In the last decade, the advance in metabolomic techniques allowed the identification of numerous individual chemicals in a small volume of biofluid.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that altered metabolism of amino acid plays an important role in the response of HNC patients to RT [36]. For example, Boguszewicz and co-workers [4] demonstrated that decreased serum level of alanine, the main substrate for gluconeogenesis during fasting and cachexia, correlated with the acute radiation toxicity-associated weight loss in HNC patients undergoing RT. The whole-body response to irradiation frequently involves molecules associated with oxidative stress and in ammation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The major bene t of RT is well established local control of the tumor. However, ionizing radiation induces damage to the adjacent healthy tissues, which is re ected at the systemic level in body uids [4][5][6][7]. Hence, detection in the patient's blood of molecular ngerprint of the body response to the treatment, which could potentially enable monitoring and prediction of radiation toxicity, is another important aspect of HNC diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…The elucidation of the molecular mechanisms of sarcopenia and cachexia is important to prevent the process of skeletal muscle atrophy and, consequently, improve the survival of cancer patients [4,5]. In this context, many studies have been interested in identifying circulating markers of muscle wasting process during cancer cachexia in clinical [6][7][8][9] and preclinical [10][11][12] models.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics studies have revealed a distinct plasma, serum, and urine metabolic profile of cancer cachexia patients [6,7]. Additionally, Boguszewicz and colleagues [8] described serum metabolic alterations as a characteristic for malnutrition or cachexia that can already be detected at the beginning of the treatment of head and neck squamous cell carcinoma patients. Miller and colleagues [9] identified candidate markers of weight loss in patients with upper gastrointestinal cancer and the assessment of the therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%